Further evidence for the existence of a viral envelope protein defect in the Bryan high-titer strain of Rous sarcoma virus. - Ogura, H (1975)
Electron microscopy observations of purified Bryan high-titer Rous sarcoma virus (BH RSV) using the freeze-drying technique showed that progeny made in the absence of a helper virus lacked visible surface projections or spikes. Phenotypic mixing experiments employing BH RSV and a thermolabile mutant of vesicular stomatitis virus, tl 17, yielded no evidence of pseudotype formation. Since tl 17 is known to be defective for an envelope glycoprotein, the lack of successful phenotypic mixing with BH RSV is consistent with the observed absence of viral spikes.